2021
DOI: 10.1093/nar/gkab281
|View full text |Cite
|
Sign up to set email alerts
|

In vivotargets ofSalmonellaFinO include a FinP-like small RNA controlling copy number of a cohabitating plasmid

Abstract: FinO-domain proteins represent an emerging family of RNA-binding proteins (RBPs) with diverse roles in bacterial post-transcriptional control and physiology. They exhibit an intriguing targeting spectrum, ranging from an assumed single RNA pair (FinP/traJ) for the plasmid-encoded FinO protein, to transcriptome-wide activity as documented for chromosomally encoded ProQ proteins. Thus, the shared FinO domain might bear an unusual plasticity enabling it to act either selectively or promiscuously on the same cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…Deletion of proQ similarly affected levels of mgtCBR mRNA, indicating this mRNA is likely a direct target of ProQ-dependent STnc540 regulation ( Blanc-Potard and Groisman, 1997 ). Two recent reports further demonstrated that FinO-dependent sRNAs regulate copy number of plasmids carrying antibiotic resistance genes in E. coli and S. enterica ( El Mouali et al., 2021 ; Yang et al., 2021 ).…”
Section: Additional Srna Chaperone Proteinsmentioning
confidence: 95%
“…Deletion of proQ similarly affected levels of mgtCBR mRNA, indicating this mRNA is likely a direct target of ProQ-dependent STnc540 regulation ( Blanc-Potard and Groisman, 1997 ). Two recent reports further demonstrated that FinO-dependent sRNAs regulate copy number of plasmids carrying antibiotic resistance genes in E. coli and S. enterica ( El Mouali et al., 2021 ; Yang et al., 2021 ).…”
Section: Additional Srna Chaperone Proteinsmentioning
confidence: 95%
“…3C ). Mutations on the NTD RNA-binding surface cause lower intracellular levels of ProQ due to a quality control pathway that prevents cellular accumulation of defective ProQ: such molecules, as well as defective Hfq, are eliminated by the protease Lon [ 62 , 65 ].…”
Section: Proq a More Recently Ascertained Rna Interactormentioning
confidence: 99%
“…ProQ and other FinO proteins bind to similar RNA motifs. However, ProQ is able to bind to many RNAs, whereas most of the FinO proteins have a small target pool [ 63 , 65 ]. Salmonella FinO, for example, is a plasmid encoded protein that mediates the interaction between the sRNA FinP and the mRNA traJ [ 59 , 63 ].…”
Section: The C-terminal Domain Of Proqmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, asRNAs were found to be associated with Hfq in B. subtilis (Dambach et al, 2013). Finally, FinO and FopA, two members of the emerging FinO/ProQ-like RBPs, act on plasmid-encoded asRNAs (El Mouali et al, 2021;Gerovac et al, 2020;van Biesen & Frost, 1994).…”
Section: Antisense Rnasmentioning
confidence: 99%